Kredit-modullı sistemada individual oqıw processlerin shólkemlestiriwdiń pedagogikalıq mexanizmin jetilistiriw - Yesemuratov, B (SCIENCE and SOCIETY, 2023)
This article discusses the credit-module system introduced in the education system of the Republic of Uzbekistan and its importance. At the same time, it is described students' attitudes and opinions about this system.
Keywords: credit-modular system; distance learning; higher education; education; credit